THE ROLE OF AESTHETIC CULTURE IN EDUCATIONAL PROCESSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In today's New Uzbekistan, the issues of raising the aesthetic culture of the individual are considered an important factor in the process of spiritual renewal. This process requires a comparative study of the problems in the field of aesthetic culture based on modern requirements, scientific analysis, and the implementation of advanced traditions.